2015
DOI: 10.3892/ol.2015.3191
|View full text |Cite
|
Sign up to set email alerts
|

Fascin expression predicts an aggressive clinical course in patients with advanced breast cancer

Abstract: Abstract.Fascin is an actin cross-linking protein, which regulates actin dynamics and filopodia or spike formation, as well as the epithelial-mesenchymal transition, and has been implicated in cell motility. Although, fascin is pivotal in mediating the aggressive behaviour of various types of cancer, its prognostic significance according to tumour stage has yet to be evaluated. Therefore, the present study investigated fascin expression in 194 patients diagnosed with invasive ductal carcinoma of the breast bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…Fascin is widely expressed in normal mesenchymal tissues and in the nervous system, but not in normal epithelial cells. Fascin is increased in several types of cancers, such as breast, colon, esophagus, and gastric cancers [ 16 19 ]. More recently, it was reported that Fascin overexpression leads to EMT, which plays a central role in carcinoma progression and metastasis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fascin is widely expressed in normal mesenchymal tissues and in the nervous system, but not in normal epithelial cells. Fascin is increased in several types of cancers, such as breast, colon, esophagus, and gastric cancers [ 16 19 ]. More recently, it was reported that Fascin overexpression leads to EMT, which plays a central role in carcinoma progression and metastasis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our findings, Monther Al-Alwan and et al have reported a strong relationship between the expression of fascin and basal-like breast cancer (p < 0.001), negative expression of ER (p < 0.001) and PR (p < 0.020), larger tumour size (p = 0.091) and distant metastasis (p = 0.017) [25]. Some other studies have also reported higher expression of Fascin in triple negative or high grade tumours [13,14,26].…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have reported overexpression of fascin in several types of malignancies, including lung [8], colon [9], stomach [10], ovary [11] and breast [12]. Previous studies on breast cancer have shown that fascin expression was associated with poor prognosis and some studies have suggested to use fascin as a potential therapeutic target especially in triple negative tumors [13,14,15]. In this study, we tried to evaluate the expression of fascin in human breast cancer using immunohistochemistry (IHC) method and explore its correlation with clinicopathological findings.…”
Section: Introductionmentioning
confidence: 99%
“…In previous array-CGH studies, fascin showed a higher expression level in cancer specimens than that in normal specimens and dysplasia (10). Fascin has been reported to be involved in cancer invasion and has been proposed as a diagnostic marker for several tumors including breast, prostate and esophageal squamous cell carcinoma (20)(21)(22)(23)(24)(25). Nevertheless, understanding of mechanisms underlying the significance of fascin expression in cancer cells is unknown, and further studies are needed.…”
Section: Discussionmentioning
confidence: 96%